A nanoemulsão do óleo rico em canabidiol protege ratos com parkinsonismo experimental induzido por 6-ohda - Oliveira, Alfaete Vieira (2024)
Parkinson's disease (PD) is a neurodegenerative disease caused by the death of dopaminergic neurons in the substantia nigra (SN) and a decrease in dopamine levels in the striatum. 6-OHDA is used as an experimental parkinsonism model, replicating the pathophysiological findings of the disease, including motor and cognitive deficits, oxidative stress, neuroinflammation, and neuronal death. It has been demonstrated that the endocannabinoid system is dysregulated in PD, and phytocannabinoids, such as cannabidiol, play a key role in neuroprotection against these pathological processes in various central nervous system (CNS) diseases. Therefore, the present study aims to investigate the neuroprotective effect of a nanoemulsion of a cannabidiol-rich oil (ORCBD) in a 6-OHDA-induced hemiparkinsonism model. Male Wistar rats received intrastriatal injections of 6-OHDA (18 μg/3μl) in the right striatum and were treated with ORCBD at doses of 5 and 10 mg/kg intraperitoneally, 24 hours before surgery and daily for 14 days. Motor behaviors (rotarod, cylinder test, open field, and apomorphine) and non-motor behaviors (depression, memory, and olfactory deficits) were evaluated, as well as dopaminergic degeneration, astrogliosis, and microgliosis. The treatment protected against motor deficits induced by the model, such as the decrease in the number of rotations in the apomorphine challenge, an increase in the number of vertical explorations in the open field test, the number of touches with the contralateral forelimb to the lesion, and a decrease in the number of falls in the rotarod test. A neuroprotective effect was observed in non-motor behaviors, such as a shorter latency time in aversive memory, a higher recognition index in the object recognition test, improvement in the recognition of familiar sawdust in the olfactory discrimination test, and increased sucrose consumption in the evaluation of anhedonia. Treatment with ORCD10 also protected against the death of dopaminergic neurons in the striatum and decreased the number of GFAP-positive cells (astrogliosis) and Iba-1-positive cells (microgliosis) in the striatum and substantia nigra. The study demonstrated that the neuroprotective activity of ORCD10 is associated with a decrease in cells involved in the inflammatory response, leading to protection against the death of dopaminergic neurons in the striatum. These findings are responsible for the improvement of motor and non-motor behaviors, demonstrating the potential of the nanoemulsion for the treatment of patients with PD.